2013
DOI: 10.1109/tamd.2013.2275949
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Early Vocabulary Development: What Sort of Responsiveness Matters?

Abstract: Maternal responsiveness has been positively related with a range of socioemotional and cognitive outcomes including language. A substantial body of research has explored different aspects of verbal responsiveness. However, perhaps because of the many ways in which it can be operationalized, there is currently a lack of consensus around what type of responsiveness is most helpful for later language development. The present study sought to address this problem by considering both the semantic and temporal dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 39 publications
7
68
1
2
Order By: Relevance
“…Of course, infants do not learn words and referents they have not experienced. Furthermore, parents' "focusing in" on infants' attention likely provides higher-quality learning instances (35). Our results also suggest an expansion of Bergelson and Swingley (36), who found that common nouns are more referentially transparent than common nonnouns.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Of course, infants do not learn words and referents they have not experienced. Furthermore, parents' "focusing in" on infants' attention likely provides higher-quality learning instances (35). Our results also suggest an expansion of Bergelson and Swingley (36), who found that common nouns are more referentially transparent than common nonnouns.…”
Section: Discussionsupporting
confidence: 73%
“…Finally, we examined referential transparency (i.e., whether parents talk about observable referents), which is suggested to facilitate language learning (33)(34)(35). Notably, previous research examining why infants learn common nonnouns (e.g., "hi," "eat") later than common nouns found that visual copresence varied across word class (36).…”
mentioning
confidence: 99%
“…Studies have provided evidence that caregivers' contingent interactions (e.g., those that follow on the infant's focus of attention) tend to elicit more pointing and speech combinations by infants (e.g., Miller & GrosLouis, 2013;Miller & Lossia, 2013) and also lead to better language abilities later in development (McGillion et al, 2013;Rollins, 2003;Tamis-LeMonda, Bornstein, & Baumwell, 2001;Tomasello & Farrar, 1986). These results provide indirect evidence about the potential relationship between an infant's multimodal communicative ability to initiate joint attention (i.e., to communicate and influence an adult's attention regarding an intended referent) on the one hand and the infant's later language abilities on the other.…”
Section: Introductionmentioning
confidence: 99%
“…For example, would existing neural network models of learning to produce speech sounds via reinforcement, such as [35] or [36], if given realistic numbers of trials and adult reinforcement rates, also yield good fits to human data? Relatedly, future extensions of this work both on the human side and on the modeling side should take into account more detailed information about the acoustics and semantics [38] of child and adult vocalizations.…”
Section: Discussionmentioning
confidence: 99%